2020
DOI: 10.1186/s12933-020-01012-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen is associated with glucose metabolism and cardiovascular outcomes in patients with coronary artery disease

Abstract: Background: The present cohort study aims to examine the relationship between fibrinogen (Fib) levels and glucose metabolism [fasting blood glucose (FBG) and hemoglobin A1c (HbA1c)] and investigate the impact of high Fib on cardiovascular outcomes in patients with stable CAD and pre-diabetes mellitus (pre-DM) or diabetes mellitus (DM). Methods:This study included 5237 patients from March 2011 to December 2015. Patients were distributed into three groups according to Fib levels (low Fib, median Fib, high Fib) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 45 publications
4
34
0
1
Order By: Relevance
“…Previous evidences suggested that FIB was an independent risk factor of CAD development and cardiovascular events in the general population [6,7]. Similar results on the prognostic value of FIB were also observed in patients with CAD [8][9][10].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Previous evidences suggested that FIB was an independent risk factor of CAD development and cardiovascular events in the general population [6,7]. Similar results on the prognostic value of FIB were also observed in patients with CAD [8][9][10].…”
Section: Introductionsupporting
confidence: 70%
“…Aside from the positive association with all-cause and CVD mortality in general individuals [6,18,19], FIB was reported to be an independent risk factor of the occurrence and severity of CAD [20]. Further, both small sample and large epidemiological studies showed that FIB was associated with worse clinical outcomes in patients with stable CAD [10,21,22]. A recent prospective study from China indicated elevated FIB was also strongly associated with MACE risk in ACS patients, especially when complicated with DM [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, previous studies including ours have demonstrated a series of risk factors for predicting cardiovascular outcomes in subjects with pre-DM or DM. Besides traditional cardiovascular risk factors [ 19 , 28 ], numerous novel parameters, including lipoprotein(a) [ 29 ], fibrinogen [ 30 ], free fatty acids [ 31 ], cystatin C [ 32 , 33 ] and so on, have emerged as significant cardiovascular risk factors in subjects with dysglycemia. However, given the growing prevalence and the added cardiovascular burden of pre-DM and DM, new avenues for exploration of more valuable prognostic biomarkers in these conditions is of increasing interest in cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
“… 27 29 Liu et al showed that fibrinogen could be used as an independent predictor of MACEs in stable CAD patients. 30 Song et al found that the plasma FIB level is a useful biomarker to predict death or non-fatal reinfarction within 1 year in patients with NSTE-ACS undergoing PCI. 31 Mahmud et al 32 found that elevated serum fibrinogen was associated with major adverse cardiovascular events at 12 months following percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%